Nitrogen process in stormwater bioretention: effect of the antecedent dry days on the relative abundance of nitrogen functional genes. (28th July 2022) - Yao, Chen; Qingyu, Wu; Zhen, Liu; Renyu, Chen; Qihong, Cheng; Shaochun, Yuan; Qiong, Wu; Yinghui, Tang
Abstract: In this study, we evaluated the relative abundance of nitrogen functional genes ( amoA, nirK and nirS ) involved in ammonia oxidation and denitrification bacteria in laboratory-scale bioretention columns in response to environmental factors (e.g., moisture content, pH, soil organic matter, soil nitrogen) under different antecedent dry days (ADDs). We observed a decrease tendency of the relative abundance of ammonia-oxidizing bacteria at first and then increased when increasing ADDs from 1 to 22 day, while the relative abundance of denitrifying bacteria showed a downward trend. The abundance of bacteria gene amoA was positively associated with soil ammonia nitrogen concentration ( r 2 = 0.389, p < 0.05) and soil organic matter concentration ( r 2 = 0.334, p < 0.05), while the abundance of bacteria gene nirS was positively correlated with soil ammonia nitrogen ( r 2 = 0.730, p < 0.01), soil organic matter ( r 2 = 0.901, p < 0.01) and soil total nitrogen ( r 2 = 0.779, p < 0.01). Furthermore, gene counts for bacteria gene nirS were correlated negatively with plant root length ( r 2 = 0.364, p < 0.05) and plant biomass ( r 2 = 0.381, p < 0.05). Taken together, these results suggest that both nitrification and denitrification can occur in bioretention systems, which can be affected by environmental factors. HIGHLIGHTS: Different antecedent dry days (ADDs) changed the relative abundance and distribution of nitrogen functional genes in bioretention columns and affected the nitrogen removal efficiency of the bioretention columns. Ammonia-oxidizing and-denitrifying bacteria were distributed predominantly in the planting layer of the bioretention soil medium (BSM). The nirS -type denitrifiers were the main functional groups controlling nitrogen removal in bioretention, and were strongly affected by environmental factors. Graphical Abstract